2019
DOI: 10.1002/cae.22190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multimedia and seating location in academic engagement and grade performance of students

Abstract: Many universities around the world use multimedia resources in large classrooms. The purpose of this study is to determine if there is any significant influence on student academic performance due to the use of multimedia (environment and tools) and seating location. This study analyses student data on grade performance and seating location for an undergraduate course at a multimedia classroom over eight semesters. This study also analyses whether short multimedia materials attract student attention in class u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…Second, the effect of distance from the screen was explored. Joshi et al analyzed the effect of multimedia and seating factors on student engagement and found that students sitting near the multimedia screen paid more attention and performed better than those sitting in the middle [35].…”
Section: Seating Factorsmentioning
confidence: 99%
“…Second, the effect of distance from the screen was explored. Joshi et al analyzed the effect of multimedia and seating factors on student engagement and found that students sitting near the multimedia screen paid more attention and performed better than those sitting in the middle [35].…”
Section: Seating Factorsmentioning
confidence: 99%
“…Other behaviors associated with sitting near the front include attention on task (Will et al, 2020) and notetaking (Lindquist & McLean, 2011). Effects on performance and GPA are more complex, but a recent study found that class grade drops by row moving backwards (Will et al, 2020) and even in studies where students in front do not perform best, similarities are seen among students sitting in the same zone (Joshi et al, 2019). Seating preference is a complex issue, reflecting room size and design, student beliefs and locus of control (Xi et al, 2017), and regardless of where students sit, multitasking can detract from learning (Jamet et al, 2020).…”
Section: Face-to-face Classroom Behaviors and Outcomesmentioning
confidence: 99%
“…Other behaviors associated with sitting near the front include attention on task and notetaking (Lindquist & McLean, 2011). Effects on performance and GPA are more complex, but a recent study found that class grade drops by row moving backwards and even in studies where students in front do not perform best, similarities are seen among students sitting in the same zone (Joshi et al, 2019). Seating preference is a complex issue, reflecting room size and design, student beliefs and locus of control (Xi et al, 2017), and regardless of where students sit, multitasking can detract from learning (Jamet et al, 2020).…”
Section: Face-to-face Classroom Behaviors and Outcomesmentioning
confidence: 99%